2016
DOI: 10.1177/0268580916675525
|View full text |Cite
|
Sign up to set email alerts
|

The rise of individual agency in conceptions of society: Textbooks worldwide, 1950–2011

Abstract: A broadly recognized sociological insight is that rising levels of individualism increasingly characterize a growing number of countries. This article examines the extent to which schooling is altered by, and transmits, this core cultural shift. It analyzes 476 secondary school social science textbooks from 78 countries from 1950 to 2011 to see whether they increasingly portray society as made up of agentic individual actors of all sorts (e.g., children, women, minorities). It is found that emphases on older s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 48 publications
0
16
0
4
Order By: Relevance
“…We expect that future educational research will develop comparison not only between immigrants in the destination country with natives, but also with other meaningful groups, namely those who stay in their country of origin. Given the intensifying 'culture of education' across the globe (Baker 2014), which anticipates evermore educated and ambitious and agentic individuals (Lerch et al 2017), and to which not only those who move, but also those who do not move are exposed (Soysal 2015), such research is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that future educational research will develop comparison not only between immigrants in the destination country with natives, but also with other meaningful groups, namely those who stay in their country of origin. Given the intensifying 'culture of education' across the globe (Baker 2014), which anticipates evermore educated and ambitious and agentic individuals (Lerch et al 2017), and to which not only those who move, but also those who do not move are exposed (Soysal 2015), such research is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Textbooks can also be seen as indicators of the current social and political climate, and markers for how groups and/or ideas carry weight in official knowledge (Schrader and Wotipka 2011). Research investigating changes in textbooks over time has accordingly observed increased focus on human rights (Meyer, Bromley, and Ramirez 2010;Skinner and Bromley 2019), individual agency (Lerch et al 2017) and environmental issues (Bromley, Meyer, and Ramirez 2011). Changes in policies and visions do not always generate desired changes in textbooks however (Svensson 2011), and textbooks sometimes reproduce biased knowledge (Molin 2006).…”
Section: The Role Of Textbooks For Promoting Action Competence In Esdmentioning
confidence: 99%
“…They have diffused their ideas to ordinary publics through a variety of means, including public education, museums and cultural exhibits, magazines and books, international organisations and national marketing campaigns (Boli and Thomas 1999;Lerch et al 2017;Thornton et al 2015).…”
Section: Schemas Of "Development" and Perceptions Of National Hierarchymentioning
confidence: 99%